Brazilian green propolis hydroalcoholic extract as a therapeutic adjuvant to treat cutaneous leishmaniasis - Beatriz Carvalho Cunha, Marina Barcelos de Miranda, Luís Carlos Crocco Afonso, Sheila Rago Lemos Abreu, Míriam Conceição De Souza Testasicca, Gisele Rodrigues Da Silva, Sandra Aparecida Lima De Moura (Journal of Applied Pharmaceutical Science, 2020)
Cutaneous leishmaniasis is caused by Leishmania parasites. There are a limited number of drugs to treat the cutaneous leishmaniasis, and most of them cause severe adverse effects. Therefore, new therapeutic strategies to treat cutaneous leishmaniasis should be developed. In this study, a standardized Brazilian green propolis (BGP) hydroalcoholic extract (Cytopropolis®, Nectar Pharma Brazil) was evaluated as a therapeutic adjuvant, aiming at the treatment of cutaneous leishmaniasis. The antileishmanial effects of different concentrations of BGP hydroalcoholic extract (500, 250, 125, 62.5, 31.25, 15.6, 7.8, and 3.9 μg ml−1) were determined in vitro against amastigotes and promastigotes and in a murine model of leishmaniasis. High concentrations of BGP hydroalcoholic extract (500, 250, 125, and 62.5 μg ml−1) reduced the viability of promastigotes. All concentrations acted against amastigotes. BGP hydroalcoholic extract (500 and 250 μg ml−1) decreased the number of promastigotes in macrophages. In addition, after 2 weeks of oral treatment, BGP hydroalcoholic extract (250 mg/kg/day) decreased the parasites and induced the macrophage infiltration in the lesion caused by the Leishmania amazonensis on the paw of mice. BGP hydroalcoholic extract may represent a therapeutic adjuvant to treat cutaneous leishmaniasis.
Keywords: Leishmania amazonensis, propolis, macrophages.